Penegakan Hukum Tindak Pidana Korupsi Ditinjau dari Teori Efektifitas Hukum - Firnando Sinaga; Hendricus Abednego Lubis; Mustika Bunga Hijriyah (The Juris, 2023)
The default case that occurred at PT Thania Indo Jaya against 2 (two) employees out of a total of 4 (four) employees with a Specific Time Work Agreement (PKWT) who was laid off due to the co-19 pandemic, namely not giving compensation rights to these employees. In this case, the Government consistently maintains PKWT by issuing Perpu Number 2 of 2022 and Government Regulation Number 35 of 2021. This study aims to determine legal protection for PKWT employees at PT. Thania Indo Jaya Semarang and PKWT arrangements in laws and regulations, legal consequences in the event of default between the Company and employees. This study uses a type or type of normative juridical study. Data collection techniques are carried out through interviews, observation and documentation studies. The study results show that legal protection for PKWT employees at PT. Thania Indo Jaya Semarang is in the form of employment social security for employees, except for employees who are still apprentices, where employees who are still apprentices only get guarantees from the funeral service, provide work clothes and tools, and form a P2K3 team. PT Thania Indo Jaya Semarang has committed a crime (default), so that it can be subject to a maximum imprisonment of 4 (four) years and/or a maximum fine of Rp. 400,000,000;- (four hundred million rupiah). Legal consequences if there is a default in the work agreement, which in the cancellation of the agreement is regulated in Articles 1451 and 1452 KUHP.